Pengaruh Pemberian Pendidikan Kesehatan Asam Urat Terhadap Pengetahuan dan Sikap Penderita Asam Urat di Wilayah Kerja Puskesmas Gatak Sukoharjo - Utomo, Wahyu Setyo, Supratman , SKM., M. Kep. , Ph .D, Vinami Yulian, S. Kep. , Ns. , MS c (2016)
Degenerative disease is a disease which pertinent with the process of degeneration at an advanced age that lasts according to the time and age. Degenerative disease generally attacks the nervous system, blood vessels, the joints and bones. In a world the prevalence of joint diseases in particular uric acid diseases (arthritis gout) increased the number of patients up to double between the years of 1990-2010. Results of basic medical research (riskesdas) by 2013 indicate joint disease in indonesia are still fairly high. Based on data from sukoharjo public health office as well by 2014 a number of visits patient with uric acid in sukoharjo reached 1507 patients. Gatak subdistrict was the region with the most patients are 321 people. Several efforts that have been carried that grant of services in the form of medical treatment and laboratory tests. Nevertheless not enough to reduce incidence of uric acid. Purpose of this research was to determine the influence of giving health education of uric acid concerning knowledge and attitudes toward uric acid patients in local clinic (puskesmas) gatak. Type of this research was the quantitative. The research method using pre-experimental research design "one group pre and posttest design" as a group. Samples of this research amounted to 30 respondents used purposive random sampling method. Measuring instrument used a questionnaire. Analysis of data includes the analysis of univariate and bivariate analysis by using wilcoxon signed rank test. Results showed pretest value attitude 49,67 and posttest knowledge 16.60 (p-value = 0.000). In pretest value attitude 49,67 and posttest 58.50 (p-value = 0.000). Conclusion of this research was existing influence of giving health education of uric acid concerning knowledge and attitudes toward uric acid patients in local clinic (puskesmas) gatak sukoharjo.